Church as Sacrament: Gutiérrez and Sobrino as Interpreters of Lumen Gentium - Walatka, Todd (Horizons, 2015)
Vatican II's Gaudium et Spes (GS) has had an unmistakable and demonstrable impact on Latin American liberation theology. Likewise, any sufficient account of the impact of GS on the wider church would need to attend to liberation theology. This article affirms this basic point, then explores the often-underappreciated relationship between liberation theology and Lumen Gentium (LG). In particular, it investigates how Gustavo Gutiérrez and Jon Sobrino interpret a fundamental ecclesiological affirmation of LG: the church as a sacrament of salvation and unity. Gutiérrez's early work provides, and Sobrino deepens, the basic point that the church's work as a sacrament inherently demands an option for the poor. Rather than being simply part of its social teaching, this option is at the heart of the church qua church. It is essential both for an adequate interpretation of LG and for a church seeking to be a credible sign and effective instrument of salvation and unity in the world.